Hypothesised mechanisms of swimming-related death: a systematic review. Issue 22 (3rd March 2016) - Asplund, Chad A; Creswell, Lawrence L
Abstract : Background: Recent reports from triathlon and competitive open-water swimming indicate that these events have higher rates of death compared with other forms of endurance sport. The potential causal mechanism for swimming-related death is unclear. Objective: To examine available studies on the hypothesised mechanisms of swimming-related death to determine the most likely aetiologies. Material and methods: MEDLINE, EMBASE and the Cochrane Database of Systematic Reviews (1950 to present) were searched, yielding 1950 potential results, which after title and citation reviews were reduced to 83 possible reports. Studies included discussed mechanisms of death during swimming in humans, and were Level 4 evidence or higher. Results: A total of 17 studies (366 total swimmers) were included for further analysis: 5 investigating hyperthermia/hypothermia, 7 examining cardiac mechanisms and responses, and 5 determining the presence of pulmonary edema. The studies provide inconsistent and limited-quality or disease-oriented evidence that make definitive conclusions difficult. Conclusions: The available evidence is limited but may suggest that cardiac arrhythmias are the most likely aetiology of swimming-related death. While symptoms of pulmonary edema may occur during swimming, current evidence does not support swimming-induced pulmonary edema as a frequent cause of swimming-related death, nor is there evidence to link hypothermia or hyperthermia as a causal mechanism. Further higher level studies are needed.